Analisis Kesesuaian Lahan Tanaman Sengon, Cengkeh, Jagung, Bawang Merah untuk Pengembangan Pola Agroforestri di Desa Tammero’do Kabupaten Majene: Analysis of the Land Suitability Sengon, Clove, Corn, Shallot Crops for the Development of Agroforestry Patterns in Tammero'do Village, Majene Regency - Rosmaeni, Rosmaeni; Palianto, Narson; Rusmidin, Rusmidin; Idris, Andi Irmayanti (Jurnal Ecosolum, 2024)
Land suitability evaluation for agroforestry development is needed for productive and sustainable land use planning. The selection of plants that are in accordance with the biophysical conditions of the land is very important to know before determining the type of plant to be planted. The purpose of this study was to analyze the suitability of land for the development of agroforestry patterns between forestry, plantation and horticultural plants. The forestry plants evaluated were Sengon, plantation plants were Cloves, and horticultural plants were Shallots and Corn. This study used field survey and laboratory analysis methods. The actual land suitability evaluated consisted of 17 biophysical characteristics at 5 observation points in the Community Plantation Forest Area. Land suitability classes are divided into 4 classes, namely S1 (very suitable), S2 (Quite suitable), S3 (Marginally suitable) and N (Not Suitable). The results of the study showed that the actual land suitability in the Community Plantation Forest Area of Tammero'do Village class S1 was Cloves at UL2, Sengon at UL2, UL3, UL4, UL5. Class S2 is Sengon in UL1, Clove and Corn, in all land units.